2001
DOI: 10.1016/s1010-7940(00)00631-x
|View full text |Cite
|
Sign up to set email alerts
|

Flush perfusion with low potassium dextran solution improves early graft function in clinical lung transplantation

Abstract: A reduction of perioperative mortality and morbidity suggests that LPD solution has superior early graft function compared to lung preservation using EC solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 13 publications
0
42
2
1
Order By: Relevance
“…LPD single flush solution was also used for the last 34 lungs procured and transplanted into 24 patients of this study. There is considerable evidence from laboratory studies that LPD provides excellent lung preservation for up to 24 h and limits the extent of ischemic-reperfusion injury, especially when compared to EC [10,11]. Many clinical studies attempted to show a reduction in the occurrence of postlung transplant graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…LPD single flush solution was also used for the last 34 lungs procured and transplanted into 24 patients of this study. There is considerable evidence from laboratory studies that LPD provides excellent lung preservation for up to 24 h and limits the extent of ischemic-reperfusion injury, especially when compared to EC [10,11]. Many clinical studies attempted to show a reduction in the occurrence of postlung transplant graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of 8%, caused by severe ischemia-reperfusion injuries, which was observed after the use of Euro-Collins solution was abolished [18]. This observation was confirmed by Keshavjee [19] and Haverich [20] and lead to a substitution of Euro Collins by LPD.…”
Section: Discussionmentioning
confidence: 74%
“…A new preservation solution composed primarily of low potassium dextran (Perfadex1; Vitrolife, Gothenburg, Sweden) has also been developed specifically for the lung and has been implemented clinically by many centres over the past few years. Five clinical reports have compared the results of Perfadex1 to those of Euro-Collins1 (Baxter Healthcare Corp., Pharmacy Division, Deerfield, IL, USA) [27][28][29][30][31], and four of them observed significantly better lung function on arrival in the intensive care unit as well as a trend towards lower 30-day mortality and better 1-yr survival with Perfadex1 (table 1). An additional report demonstrated that after adjustment for graft ischaemic time, extracellulartype preservation solutions were associated with a decreased incidence of primary graft failure after lung transplantation when compared with intracellular-type preservation solutions such as Euro-Collins1 [32].…”
Section: Methods Of Lung Preservationmentioning
confidence: 99%